Central bank digital currency in small open economies - Rong Fan; Todd B. Walker; Allan Wright (Latin American Journal of Central Banking (LAJCB), 2025)
This paper examines how the introduction of Central Bank Digital Currency (CBDC) impacts small open economies (SOE). We build a Two-Agent New Keynesian (TANK) model with financially constrained agents, where both cash and CBDC provide liquidity service. CBDC lowers the cost of carrying liquid assets but does not provides anonymity like cash. Our main results are: (i) CBDC always increases the welfare of financially unconstrained households; however, it increases the welfare of constrained households when the cost of carrying cash is high enough and when the government purchase level is sufficiently low; (ii) CBDC increases the fiscal income by bringing more agents out of the informal economy, improving fiscal sustainability; (iii) CBDC improves the terms of trade as it strengthens the domestic currency.
Keywords: J24; J31; O11; O14; 330; CBDC; Digital currency; Fiscal policy